The Effects of Islamic Spiritual Activities on Psycho-Physiological Performance - Muhammad Nubli Abdul Wahab Urme Binte Salam (Universitas Ahmad Dahlan, 2013)
AbstractÂ In Islam, spiritual activities such as taubah and zikir are very common to the Muslim Ummah and these are generally performed to the perfection of individualâ€™s mind. In addition, it is believed that through these activities a connection can be made with the Almighty. Therefore, reasonably after the performance of these activities the psychophysiological performance of the respondents will be changed significantly. This significant change is traceable with the aid of GSR and HRV biofeedback. In this study, it is observed that remarkable changes of GSR percentage and accumulated coherence score of HRV among the 18 respondents due to the consequences of spiritual activities. Thus, it is possible to say that to make the positive changes of psychophysiological activities of any individuals spiritual activities may considered as a substantial stimuli in psychophysiological research.Â Keywords: psychophysiology; GSR; HRV; Biofeedback; Spiritual activity